2017
DOI: 10.1186/s12936-017-1815-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunity as a predictor of anti-malarial treatment failure: a systematic review

Abstract: BackgroundNaturally acquired immunity can reduce parasitaemia and potentially influence anti-malarial treatment outcomes; however, evidence for this in the current literature provides conflicted results. The available evidence was synthesized to determine and quantify the association between host immunity and anti-malarial treatment failure.MethodsFour databases were searched to identify studies investigating malaria antibody levels in patients receiving anti-malarial treatment for symptomatic malaria with tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Overall, signal intensities of younger participants were lower than those of older participants. Normalizing the mean signal intensities to P falciparum proteins from participants at varying ages against the mean intensities for the oldest subject group revealed that the magnitude of antibody responses to these antigens increased with age ( These findings suggest that antibody responses associated with nPC-ACPR are acquired over time through repeated exposures as children age into adults, thus corroborating previous studies (4,18,19).…”
Section: Antibody Responses Associated With Npc-acpr Are Age Dependentsupporting
confidence: 83%
“…Overall, signal intensities of younger participants were lower than those of older participants. Normalizing the mean signal intensities to P falciparum proteins from participants at varying ages against the mean intensities for the oldest subject group revealed that the magnitude of antibody responses to these antigens increased with age ( These findings suggest that antibody responses associated with nPC-ACPR are acquired over time through repeated exposures as children age into adults, thus corroborating previous studies (4,18,19).…”
Section: Antibody Responses Associated With Npc-acpr Are Age Dependentsupporting
confidence: 83%
“…The immune-modulating potential of the decoction was performed by comparing hematological results of the standard treated mice with the control. It has been reported in studies that for an effective cure of malaria, the immunity of a person is an important factor [7]. Assessment of total white blood cell counts has shown elevated levels to a group that used a combination (A/LU + CILI extract).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment failure due to artemisinin-based combination therapies (ACTs) has been attributed to its uneven pharmacokinetics among individuals and its requirement to be taken with a fatty meal to improve absorption [5,6]. Moreover, the dosage, the compliance and the immune status of the patient are all implicated [7]. Failure may also happen in immune-compromised patients as they are likely to be taking other medications like efavirenz.…”
Section: Introductionmentioning
confidence: 99%
“…Such immunity is related to the degree of adherence to control measures, and analysis of antibody responses to validated antigens could be an indirect way of tracking compliance to measures such as LLINs which is the largest contributor to sustained protection [2]. Importantly, immunity affects treatment outcome with a significant impact when using the current first-line artemisinin combined treatments [38]. Monitoring of parasite clearance times in symptomatic malaria, which is routinely done in Côte d'Ivoire, is [6].…”
Section: Discussionmentioning
confidence: 99%